10-year beverage intake trends among U.S. preschool children: Rapid declines between 2003 and 2010, but stagnancy in recent years - Ford, Christopher N. (Pediatr Obes, 2015)
BACKGROUND: It has been previously reported that total energy intake among U.S. preschool children (ages 2–5y) decreased between 2003–04 and 2009–10. However, little is known about how intakes of beverages among U.S. preschoolers (ages 2–5y) changed from 2003–04 through 2011–12. This paper examines changes in intakes of key beverages during this period, as well as how eating location (at home or away from home) and source (store vs others) may have contributed to these changes. METHODS: Cross-sectional day one dietary data among children ages 2–5y from the National Health and Nutrition Examination Survey (NHANES) 2003–04, 2005–06, 2007–08, 2009–10 and 2011–12 were used. Survey-weighted mean intakes by survey year, eating location, and source, were computed for total sugar sweetened beverages (SSBs), milks, 100% juice, low/no-calorie beverages, 10 key beverages, total beverages and total foods. Means were compared using two-tailed z-tests with Bonferroni corrections (α<0.05). RESULTS: Between 2003–04 and 2011–12, among 2–5 year olds, total caloric intake fell by 132 kcal/d, with intakes of beverages falling by 55 kcal/d. Decreases in intakes of total SSBs (−57 kcal/d), fruit-flavored or juice drinks containing <100% juice (juice drinks) (−37 kcal/d), caloric soft drinks (−13 kcal/d), and >1% fat, low-sugar milk (−42 kcal/d) were among the major changes. By eating location, total beverage intake at home fell by 73 kcal/d. By source, total beverage intake from stores fell by 106 kcal/d. Changes in intakes occurred primarily between 2003–04 and 2009–10, as there were no significant differences in beverage intakes between 2009–10 and 2011–12. Intakes of total calories (+49 kcal/d), and calories from foods (+53 kcal/d), trended upward between 2009–10 and 2011–12, but changes were not significant. CONCLUSIONS: These findings suggest improvements in the diets of preschoolers between 2003–04 and 2009–10, of which stores were a major contributor.